Factors associated with sanitation practices among hospital foodservice workers in East Java - Sinaga, Tiurma 1961-; Gatchalian, Corazon F. (1992)
The study focused on factors associated with sanitation practices in food preparation and food production among foodservice workers of two hospitals in East Java, Indonesia. The characteristics of foodservice workers, i.e. socio-demographic characteristics, sanitation knowledge and organizational variables, i.e. extent of supervision and type of hospital are hypothesized to be significantly related with sanitation practices. A self-administered questionnaire was used to collect data. This was pretested at a private hospital in Malang, Indonesia. Using Cronbach's formula for internal consistency, a reliability coefficient of .8603 was obtained. Criterion-related validity was measured resulting in a validity coefficient of .46132. Using simple random sampling, 129 foodservice workers- 48 from Dr. Saiful Anwar Hospital and 81 81 from Dr. Soetomo Hospital were chosen as respondents. Both descriptive and inferential statistical techniques were used. Using F-test and t-test, the study showed no significant relationship between age, educational attainment, length of service, and extent of supervision on implementation of sanitation policies and procedures with sanitation knowledge and sanitation practices. A highly significant relationship was found between sex, and sanitation knowledge with females having higher scores than males. The same variable is also found to be highly associated with sanitation practices, since females have higher sanitation practice scores than their counterparts. Likewise, sanitation knowledge was found to be significantly associated with sanitation practices of the foodservice workers at .01 level of significance. Type of hospital is also greatly associated with extent of supervision on the implementation of sanitation policies and procedures. Given the results of the study, it is recommended that further research be done to cover a broader scope of activities in the foodservice establishment, i.e. food receiving, food distribution, food service, etc. Other variables, i.e. attitude, level of sanitation awareness, motivation and morale, adequacy of physical facilities and equipment could also be investigated. An in depth study on knowledge and practices could also be done to identify possible training needs on sanitation. Likewise, studies may include all categories of hospitals in Indonesia, public as well as private, and related establishments such as college/ school foodservices. These would help for more conclusive evidences on the subject of inquiry and guide decision-making on the matter. Although extent of supervision did not show any significant relationship with sanitation knowledge and sanitation practices, a similar study to be conducted on supervisors could give valuable information which could guide hospitals in determining future courses of action related to recruitment, evaluation and training, and institution of policies and guidelines. The formulation of appropriate policies and guidelines on sanitation as well as strict monitoring of its implementation is further recommended. At the national level, it is recommended that the Indonesian government institute clear cut policies and standards on sanitation in all hospitals, both public and private.
Computer print-out.
Thesis (M. Food Service Administration)--University of the Philippines, Diliman.
Vita.
Keywords: Food service -- Sanitation -- Indonesia; Food handling -- Indonesia; Food service employees -- Indonesia; Hospitals -- Food service -- Indonesia